PERAN TEMPE KEDELAI HITAM TERHADAP INDEKS STIMULASI PROLIFERASI SEL T, KADAR IL-2 DAN KADAR GLUTAMIN PADA TIKUS SECARA IN VIVO - Nurrahman -; Nurhidajah - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Consumption of black soybean tempe effected on macrophage activity and increased levels of IL - 1 . Increased activity of macrophages positively correlated to the amount of IL- 1 . The purpose of this study was to determine the role of black soybean tempe against T cell proliferation stimulation index , levels of IL - 2 and glutamine levels on rats, in vivo. A number of 30 rats were grouped into 5 ( five ), 6 rats for each group. Rats are placed in individual cages and room temperature ( 25 - 27oC ) . Maintained for 30 days each group was treated by administering a standard diet and diet plus flour of soybean black tempe ( 25 , 50 , 75 and 100 % instead of casein ) . The research results showed that consumption of black soybean tempe effected on T-cell proliferation stimulation index, levels of IL – 2, and levels of glutamine. Increased T cell proliferation stimulation index is positively correlated to the amount of IL- 2 .Keywords: black soybean tempe, T cell, interleukin 2, glutamine